Employee Workload Analysis Using the Full-Time Equivalent Approach at PT Pupuk Sriwidjaja Palembang - Basuki, Mahmud; Rohman, Mohamad Fatchur; Hermanto; Azzat, Noor Nailie (Journal of Industrial Engineering and Halal Industries, 2025)
This study aims to calculate and analyze workload at PT Pupuk Sriwidjaja Palembang, specifically within the Field Technical Inspection Group II of the Technical Inspection department. The research was conducted by determining the appropriate number of workers based on their work output and effective working hours. The study was motivated by the observation that there is often idle time and a high frequency of off-site activities among employees in the technical inspection section. The Full-Time Equivalent (FTE) method was used to analyze the workload distribution and employee productivity. Based on the 2019 data, effective working hours were calculated to be 5.6 hours per day, with a total of 238 working days in the year. The results show that employee productivity is generally high. However, three employees were found to be overloaded, with FTE index values of 1.281, 1.327, and 1.302, indicating excessive workload. Meanwhile, eight employees had normal FTE index values ranging from 1.054 to 1.255. The findings can be used to improve workload distribution and staffing decisions within the department.